Novel Approaches in Primary Cardiovascular Disease Prevention: The HOPE-3 Trial Rationale, Design, and Participants' Baseline Characteristics - Lonn, E.; Bosch, J.; Pogue, J.; Avezum, A.; Chazova, I.; Dans, A.; Diaz, R.; Fodor, G.; Held, C.; Jansky, P.; Keltai, M.; Keltai, K.; et al. (2015)
BACKGROUND: Cholesterol and blood pressure (BP) can be effectively and safely lowered with statin drugs and BP-lowering drugs, reducing major cardiovascular (CV) events by 20%-30% within 5 years in high-risk individuals. However, there are limited data in lower-risk populations. The Heart Outcomes Prevention Evaluation-3 (HOPE-3) trial is evaluating whether cholesterol lowering with a statin drug, BP lowering with low doses of 2 antihypertensive agents, and their combination safely reduce major CV events in individuals at intermediate risk who have had no previous vascular events and have average cholesterol and BP levels. METHODS: A total of 12,705 women 65 years or older and men 55 years or older with at least 1 CV risk factor, no known CV disease, and without any clear indication or contraindication to the study drugs were randomized to rosuvastatin 10 mg/d or placebo and to candesartan/hydrochlorothiazide 16/12.5 mg/d or placebo (2 × 2 factorial design) and will be followed for a mean of 5.8 years. The coprimary study outcomes are the composite of CV death, nonfatal myocardial infarction (MI), and nonfatal stroke and the composite of CV death, nonfatal MI, nonfatal stroke, resuscitated cardiac arrest, heart failure, and arterial revascularization. RESULTS: Participants were recruited from 21 countries in North America, South America, Europe, Asia, and Australia. Mean age at randomization was 66 years and 46% were women. CONCLUSIONS: The HOPE-3 trial will provide new information on cholesterol and BP lowering in intermediate-risk populations with average cholesterol and BP levels and is expected to inform approaches to primary prevention worldwide (HOPE-3 ClinicalTrials.govNCT00468923).